The Blind in French Society : From the Middle Ages to the Century of Louis Braille. - Weygand, Zina (Stanford University Press, 2009)
A history of perceptions of the blind and of their integration or lack thereof in French society, this book introduces us to a host of fictional and real individuals and paints a moving picture of their advances and disappointments, concluding with the triumphant invention of Louis Braille.